2011
DOI: 10.4172/1948-5956.s1-003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Study of Proteins in Prostate Cancer and Benign Hyperplasia Cells

Abstract: Comparative proteomic studies of proteins in DU-145, PC-3, LNCaP and BPH-1 cultivated cells as well as in prostate tissue samples obtained from patients with benign and malignant tumors showed differences in protein profiles, in particular, high content in tissue samples of four isoforms of transgelin and profilin-1. Increased expression of protein Dj-1 was observed in cancer cells and biopsy samples of prostate cancer as opposed to BPH-1 cells and biopsy samples of tissues with benign hyperplasia. Dramatic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Using proteomic technologies (two-dimensional electrophoresis (2-DE) and mass-spectrometric identification) the authors revealed that Cfl-1 was involved in processes of cell differentiation in colorectal adenocarcinoma (Caco-2) cell line. Later, Cfl-1 was identified in different tumor cell lines and tissues including adenocarcinomas [ 15 , 140 , 141 , 142 , 143 ], osteosarcoma [ 144 ], lymphoid tissue neoplasms [ 145 ], astrocytoma [ 146 ], glioma [ 147 ], and neuroblastoma [ 148 ]. Accordingly, it is possible to think that Cfl-1 is a common participant in various tumor phenotypes.…”
Section: Members Of the Actin-depolymerizing Factor/cofilin Superfmentioning
confidence: 99%
See 2 more Smart Citations
“…Using proteomic technologies (two-dimensional electrophoresis (2-DE) and mass-spectrometric identification) the authors revealed that Cfl-1 was involved in processes of cell differentiation in colorectal adenocarcinoma (Caco-2) cell line. Later, Cfl-1 was identified in different tumor cell lines and tissues including adenocarcinomas [ 15 , 140 , 141 , 142 , 143 ], osteosarcoma [ 144 ], lymphoid tissue neoplasms [ 145 ], astrocytoma [ 146 ], glioma [ 147 ], and neuroblastoma [ 148 ]. Accordingly, it is possible to think that Cfl-1 is a common participant in various tumor phenotypes.…”
Section: Members Of the Actin-depolymerizing Factor/cofilin Superfmentioning
confidence: 99%
“…The accumulated data suggests that changes in cell motility can be triggered by certain actin-binding proteins (ABPs) which provide the formation, function, and restructuring of the actin cytoskeleton [ 10 , 11 , 12 , 13 ]. The detection of these changes allows the clarification of the molecular basis of malignant transformation and the role of certain proteins (in particular, ABPs) in this process [ 11 , 12 , 13 ], and, in addition, allows the list of potential tumor biomarkers to expand [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that such molecules could be potential biomarkers and/or targets for chemotherapy. The use of malignant cell lines and technologies of modern biochemistry is an effective basis for searching for key molecules ex vivo [77][78][79][80][81][82] . Ex vivo culture systems in experimental oncology are also used for study of potential anticancer drugs.…”
Section: Human Malignant Cells and Post-genomic Technologies In Expermentioning
confidence: 99%